Validation of the CAT rapid: a smartphone screening tool for HIV-associated neurocognitive disorders in South Africa - Witten, Jade Abigail (Department of Psychology, 2015)
Existing screening tools are not suitable for the detection of HIV-associated neurocognitive disorders (HAND) in South Africa. Study 1 of the current thesis aimed to establish construct validity of a new screening tool, the Cognitive Assessment Tool-Rapid(CAT-Rapid), in a sample of cognitively healthy South African undergraduates (n = 122).Study 2 investigated the tool¡¯s diagnostic validity in a sample of HIV-positive adult South Africans (n = 89). In Study 1 and Study 2, correlational analyses characterizing the associations between CAT-Rapid subtests and analogous standardized neuropsychological tests sought to establish construct validity. In Study 2, ROC curves, and estimates of sensitivity and specificity values, characterized the CAT-Rapid¡¯s diagnostic validity. Results from Study 1 demonstrated adequate construct validity for the CAT-Rapid in the cognitively healthy sample. Results from Study 2 did not demonstrate construct validity of the tool in the clinical sample. Regarding diagnostic properties, at the recommended cut off score ¡Ü 10, the CAT-Rapid did not demonstrate optimal sensitivity and specificity in the detection of HAND. Future research should investigate how the CAT-Rapid compares to paper-and-pencil screening tests that have demonstrated promising results in studies emerging from the global north.